Savremeni jezički korpusi na Zapadnom Blakanu - Dobrić, Nikola (Slavistična revija, 2012)
The West Balkans have had a rich history in developing language corpora. The first electronic corpus in the region was created only a few years after thevery first one in the world, while the idea of developing electronic language resources dates even further back. This early development of natural language processing was somewhat hampered by the unfortunate events of the 1990s, but in the last two decades there has been some substantial improvement in the development of the West Balkan language corpora. The paper presents a historical overview of the language corpora development in the region in the period from 1950 to 1990 as well as its current state and future prospects.
Keywords: corpora; corpus linguistic; Corpus linguistics; Croatian language; history; hrvarščina; jezikovni korpusi; južnoslovanski jeziki; korpusi; korpusna lingvistika; language resources; linguistic corpora; natural language processing; Serbian language; Slovene; Slovenian languge; slovenščina; South Slavic languages; srbščina; West Balkan; zahodni Balkan; zgodovinski pregledi